2014
DOI: 10.1038/srep04867
|View full text |Cite
|
Sign up to set email alerts
|

The junctional epithelium originates from the odontogenic epithelium of an erupted tooth

Abstract: The junctional epithelium (JE) is an epithelial component that is directly attached to the tooth surface and has a protective function against periodontal diseases. In this study, we determined the origin of the JE using a bioengineered tooth technique. We transplanted the bioengineered tooth germ into the alveolar bone with an epithelial component that expressed green fluorescence protein. The reduced enamel epithelium from the bioengineered tooth fused with the oral epithelium, and the JE was apparently form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…However, there was no obvious difference in the morphology of JE among the three groups after wound healing; the fast ability of JE to self-renew may be the most likely explanation for our results. 43 , 44 The self-renewal time of the normal JE is 1–6 days. Therefore, it is difficult to distinguish them morphologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no obvious difference in the morphology of JE among the three groups after wound healing; the fast ability of JE to self-renew may be the most likely explanation for our results. 43 , 44 The self-renewal time of the normal JE is 1–6 days. Therefore, it is difficult to distinguish them morphologically.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our data revealed that the colocalization band, indicating HDs first formed in the coronal region of the JE, since the cells directly attached to the tooth, migrates and adheres toward the crown. 44 To verify the efficacy of epithelial reattachment, we adopted the HRP-penetration assay to assess the biological sealing of the tooth–JE interface. 49 From the penetration distance of the HRP reaction, the Ad-LAMA3 group exhibited higher biological sealing capacity than the saline and Ad-GFP groups.…”
Section: Discussionmentioning
confidence: 99%
“…JE is a special tissue of odontogenic origin which includes post‐functional ameloblasts of the epithelium of reduced the enamel organ . Once the formation of enamel matrix is concluded, these cells turn into reduced ameloblasts that become part of the reduced enamel epithelium . This epithelium wraps the crown, and when the tooth is about to erupt, unites with the basal cells of the gingival epithelium allowing the tooth eruption and creating the final mature JE …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epithelial cells from mouse embryos have been showed to result in the tooth like frameworks if joined with embryonic dental mesenchyme, however, not whole functional teeth [42][43][44]. Yajima-Himuro et al [45] have transplanted bioengineered tooth germ into the alveolar bone with an epithelial component, and concluded that epithelium from the bioengineered tooth fused with the oral epithelium, and the junctional epithelium was apparently formed around the bioengineered tooth 50 days after transplantation.…”
Section: Provenance Of Dental Stem Cellsmentioning
confidence: 99%